Convergence of a short-step primal-dual algorithm based on the Gauss-Newton direction - Serge Kruk; Henry Wolkowicz (Journal of Applied Mathematics)
We prove the theoretical convergence of a short-step, approximate path-following, interior-point primal-dual algorithm for semidefinite programs based on the Gauss-Newton direction obtained from minimizing the norm of the perturbed optimality conditions. This is the first proof of convergence for the Gauss-Newton direction in this context. It assumes strict complementarity and uniqueness of the optimal solution as well as an estimate of the smallest singular value of the Jacobian.